(3GdfhGRds - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdnqSnerQnbrfOj, CHh GddjK, GdedbH HEeGe GdgOi,J (B373 (3g` s
(3ChdgG (B:s
(3cJGH GdfhGRd ddTjN GdEeGe CHj GddjK Gdabjg GdSeQbfOi GdeYQha HEeGe GdgOi hgh Chd cJGH LeY ajg GdhGbYGJ GdJi de jhLO ajgG QhGjI GdCFeI GdKdGKI s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HChdg agQSJs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs